Exploring the association between deep learning approach, problem-solving skills, digital literacy, and student learning outcomes: a data-driven nonparametric study in science education - Eviana; Achmadi; Afandi (CV. FOUNDAE, 2026)
Background: The demands of 21st-century education require students to possess higher-order thinking skills, particularly problem-solving abilities, along with adequate digital literacy and optimal academic achievement. However, these competencies are often underdeveloped due to the continued use of surface-level instructional approaches that limit meaningful learning engagement. Aims: This study aims to examine the association between the deep learning approach, problem-solving skills, digital literacy, and student learning outcomes, as well as to provide empirical evidence of the interrelationships among these variables in the context of science education. Method: A quantitative correlational design was employed involving 121 tenth-grade students selected through proportionate random sampling from a population of 199 students. Data were collected using validated questionnaires measuring the deep learning approach, problem-solving skills, digital literacy, and learning outcomes. Prior to analysis, validity and reliability tests were conducted. Due to the non-normal distribution of one variable, Spearman’s Rho correlation analysis was applied. Results: The findings revealed significant positive correlations between the deep learning approach and problem-solving skills, as well as digital literacy, both indicating moderate relationships. A weaker but statistically significant correlation was found between the deep learning approach and learning outcomes. Additionally, problem-solving skills and digital literacy demonstrated the strongest relationship among the variables. Conclusion: These findings suggest that the deep learning approach is closely associated with the development of higher-order thinking and digital competencies, although its direct relationship with learning outcomes is limited. Therefore, integrating deep learning strategies with problem-solving and digital literacy activities is essential to enhance students’ readiness for 21st-century learning.